Receptor‐Spacer‐Fluorophore Based Coumarin‐Thiosemicarbazones as Anion Chemosensors with "Turn on" Response: Spectroscopic and Computational (DFT) Studies. Issue 26 (11th July 2018) - Islam, Muhammad; Hameed, Abdul; Ayub, Khurshid; Naseer, Muhamamd Moazzam; Hussain, Javid; Alharthy, Rima D.; Asari, Asnuzilawati; Ludwig, Ralf; Rashida, Mariya al‐; Shafiq, Zahid
Abstract: Anion sensing via small molecules as chemosensor carries unique significance in biological and environmental fields, where it offers several advantages over the traditional methods of ion sensing. In the current study, the receptor ‐ spacer ‐ fluorophore based coumarin thiosemicarbazones were synthesized and investigated as chemosensor against different anions. The anion interaction with thiosemicarbazone based receptors (ligands) was observed and investigated with naked‐eye and by using UV‐Visible, fluorescence and 1 H NMR spectroscopic techniques. The deprotonation of NH protons upon binding with F̄ was confirmed via 1 H NMR spectroscopic data. Binding constants and limit of detection was also calculated. Theoretical studies via DFT calculations were also carried to understand the ligand‐anion interaction. The theoretical and experimental data was found to be in agreement, confirming the anion mediated NH proton abstraction as the mechanism that is responsible for anion sensing. Furthermore, the reason (and mechanism responsible) for anion selectivity exhibited by these chemosensors was also investigated computationally. Abstract : Coumarin based thiosemicarbazones were investigated as chemosensor against various anions. The receptors‐anions interaction was studied via naked‐eye and various spectroscopic techniques include UV‐Visible, fluorescence and 1 H NMR spectroscopic techniques. The spectral data results showed deprotonation of N‐ H protons upon binding with F̄ anion. Binding constants and limit of detection was also calculated. Theoretical studies via DFT calculations were also carried to understand the ligand‐anion interaction.